(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Effective facility design and unit-load formation are critical factors in optimizing modern warehouse operations and minimizing supply chain costs. While various handling equipment options exist, pallets serve as the primary structural foundation for maximizing storage and transport efficiency. This study outlines a systematic approach to equipment selection and dimension optimization within a large-scale industrial warehouse design. It evaluates pallet material performance across wood, plastic, and metal alternatives. To overcome the challenges of standardizing handling procedures, two distinct optimization workflows—Linear Programming (LP) and Space Utilization Efficiency (SUE)—are examined to identify the ideal footprint for uniform racking configurations. Comprehensive inventory modeling is then applied to calculate total pallet capacity constraints under specified load weights, height boundaries, and stack ability limits. Based on structural and economic parameters, premium wooden pallets measuring 1000mm X 900mm X 150mm were selected, achieving an optimal spatial efficiency of up to 94.4% for core inventory components. To fully support the facility's inventory demands across nine distinct material classes, the total fleet requirement was mathematically determined. The logistics analysis indicates that the warehouse requires a total infrastructure capacity of 185,663 standardized pallets, comprised of 181,376 units for primary cycle and safety stock alongside 4,287 units for dedicated buffer operations. Implementing this uniform pallet standard minimizes floor space loss, simplifies shelf design, and establishes a highly streamlined material handling workflow.